1995
DOI: 10.1042/bj3120833
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive nuclear NFκB/rel DNA-binding activity of rat thymocytes is increased by stimuli that promote apoptosis, but not inhibited by pyrrolidine dithiocarbamate

Abstract: Rat thymocytes spontaneously undergo apoptotic death in cell culture, and are also sensitive to the induction of apoptosis by various stimuli. We show that unstimulated thymocytes constitutively express a p50-containing nuclear factor kappa B (NF kappa B)/rel DNA-binding activity in their nuclei. When the cells were fractionated by density-gradient centrifugation this activity was found to be most pronounced in immature CD4+8+ thymocytes, the cell population that undergoes selection by apoptosis in vivo and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 46 publications
(62 reference statements)
4
10
0
Order By: Relevance
“…The expression of BAD was previously reported to be induced by either etoposide or TRAIL which were also shown to increase the transcriptional activity of NF-κB. The detailed mechanism was however not suggested (29)(30)(31)(32). The regulatory effect of NF-κB on BCL-2 family members has been suggested by many investigators.…”
Section: Discussionmentioning
confidence: 93%
“…The expression of BAD was previously reported to be induced by either etoposide or TRAIL which were also shown to increase the transcriptional activity of NF-κB. The detailed mechanism was however not suggested (29)(30)(31)(32). The regulatory effect of NF-κB on BCL-2 family members has been suggested by many investigators.…”
Section: Discussionmentioning
confidence: 93%
“…Etoposide and vincristine, chemotherapeutic agents that induce apoptotic cell death, also activate NF-kB, although binding to a distinct receptor. 29,36) These anticancer agents may be less effective at inducing apoptotic cell death because of the concomitant activation of NF-kB. 36) Disruption of the protective mechanism induced by NF-kB makes cells much more vulnerable to killing by TNF-a and other chemotherapeutic agents and ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…126 Moreover, mitoxantrone, which is unable to undergo redox cycling, was also found to activate NF-B in a pyrrolidine dithiocarbamate-insensitive manner, suggesting that the inhibitory effect of pyrrolidine dithiocarbamate could not be related to its antioxidant property. 129 CER was also a plausible candidate. Indeed, previous studies have shown that the addition of CER induced NF-B activation.…”
Section: Implication Of Nf-b Activation In Dnr-induced Apoptosismentioning
confidence: 99%
“…88 By using electrophoretic mobility shift assays, it has been shown that NF-B DNA binding activity is stimulated by cytotoxic effectors, including DNA-damaging agents, such as ionizing radiation, alkylating agents, anthracyclines, topoisomerase inhibitors, and cytosine arabinoside. 89,[123][124][125][126][127][128][129][130] However, the fact that nongenotoxic anticancer compounds such as vinca alkaloids and taxanes 125 may also activate NF-B suggests that DNA damage is not necessarily needed for drug-induced NF-B activation. This finding could mean that these drugs share some NF-B-activating signaling pathways that can be generated in the cytosol but not in the nucleus, similar to that observed in the UV response in which NF-B activation was clearly demonstrated to be initiated not in the nucleus but at or near the plasma membrane through a Src-and Ras-dependent mechanism.…”
Section: Implication Of Nf-b Activation In Dnr-induced Apoptosismentioning
confidence: 99%